Conservation and Development of Koh Kret Community Environment in Nonthaburi - Phattanawasin, Srisak (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The expansions of urbanization and economic growth over Bangkok area generate rapid changes on several small communities surrounding Bangkok, especially on the potential ones such as Koh Kret, Nontahburi. Due to its unique physical, social and cultural virtues, Koh Kret has been promoted as an eco-cultural tourist attraction. This, to some extent, has impacts on Koh Kret’s physical transformations concerned with their original way of life and cultures, causing the difficulties between retaining the cultural heritage and modernizing the community area. This research had studied on both theoretical and related topics along with a field research, focusing on the studies for conservation and sustainable development of Koh Kret community environment related to the tourism. Two main issues were covered in this research, that is, the community planning and the vernacular architecture. In this study, the participating research was performed by using field surveys and questionnaires for gathering information on community attitudes toward the above issues. This could be useful to identify the solution approaches directed to the community problems. The approaches for conservation and development of Koh Kret community environment as shown in this research could be further used to design a policy that can be implemented in practical use for the community.